The Sulu-China connections past and present - Asain, Calbi A. (2004)
The contact between Sulu and China, or the Tausugs and Chinese, appears to be one of the longest, if not the longest, in Filipino cultural and historical experience. It dates back to time immemorial long before the Spaniards and other colonizers braved our present-day Philippines. It is, therefore, interesting to revisit it and to mark its contributions to Tausug-Muslim-Filipino culture and history. Today, the Chinese in Sulu have endured and survived difficult and challenging realities. Some may have already left, but others have decided to stay. Those who have remained are the living witnesses to the cultural and historical ramifications of the Tausug-Chinese interaction-past and present-and how it has been enhanced and nurtured by marital and economic ties and reciprocal respect for each other's cultural uniqueness.
Includes bibliographical references (pages 96-97).